Performance of pea ( Pisum sativum) cultivars and lines in Pelotas, Rio Grande do Sul - Oliveira, Heitor Amaral; Santos, Alverides Machado dos (Pesquisa Agropecuaria Brasileira, 2014)
This paper deals with the results obtained in the studies of cultivars and strains of peas for canning held at Pelotas, Rio Grande do Sul, during the years of 1968 and 1970. Taking into consideration only the seed yields obtained, the strains 1,100-16, C-90 e 1,100-8 were significantly superior to the cultivars Res. Early Perfection 326 and Roi des Fins Verts extensively used in the pea production regions of the State of Rio Grande do Sul. All cultivars studied were classified as medium size and medium cycle maturity.